The Effect of Therapeutic Exercises on the Rehabilitation of Partial Achilles Tendon Rupture in the Ankle Joint Among Football Players - Khalif , Emad (Journal of Physical Education, 2025)
The participation in the rehabilitation of injuries among athletes and non-athletes from various sports, as well as the prevention and reduction of sports injuries and the restoration of athletes to their pre-injury condition, represent a fundamental goal in the sports field. Progressive rehabilitative exercises, applied from simple to complex, play a crucial role in restoring function and reducing pain among injured athletes. This study aimed to design and implement rehabilitation sessions composed of targeted exercises to treat partial Achilles’ tendon rupture in football players and to examine the differences between pre- and post-tests in static strength and balance. Using an experimental one-group pre–post design, the researcher applied the program to five football players aged 20–23 years, ensuring all exercises were performed correctly within the planned schedule. The results indicated that the rehabilitative exercises had a positive effect on balance and the studied physical attributes, enabling the players to return safely to play and competition. The study recommends adopting the proposed rehabilitation approach and emphasizes the importance of early treatment and rehabilitation of Achilles tendon injuries among football players.